Unilateral Cordotomy: A Systematic Review of Efficacy and Outcomes. (7th March 2022) - Talmor, Guy; Tseng, Christopher; Nguyen, Brandon; Badash, Ido; Lovinescu, Corina Din; Benson, Brian; Kaye, Rachel
Abstract : Introduction: Glottic obstruction may arise secondary to bilateral vocal fold immobility (BVFI). Treatment options include a tracheostomy to bypass the site of obstruction as well as unilateral transverse cordotomy to alleviate the obstruction. The objective of this review is to determine the efficacy, adverse event profile, and long‐term outcomes, including the need for tracheostomy, in patients undergoing unilateral cordotomy. Methods: The Preferred Reporting Systems for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines were followed for this systematic review. A literature search of unilateral cordotomy was performed by searching PubMed, Cochrane Library, and Embase. Articles presenting cases of BVFI treated with unilateral cordotomy were included. Review articles, animal studies, non‐English‐language articles, and abstracts were excluded. Articles presenting cases of bilateral cordotomy or cordotomy with arytenoidectomy were excluded. Results: We identified 14 studies and 291 patients undergoing unilateral cordotomy. Sixty‐eight patients had a prior tracheostomy in place at the time of cordotomy. The most common post‐operative complication was granulation tissue formation ( n  = 39). Thirty‐one patients developed glottic edema with subsequent dyspnea. Three patients developed scarring of the primary cordotomy site with the return to an obstructed airway. Nine patients required a post‐cordotomy tracheostomy due to these complications. Five patients required a long‐term tracheostomy and were unable to be decannulated. Conclusion: Unilateral cordotomy is an effective treatment for glottic obstruction with high post‐operative decannulation rates. Adverse events including worsening glottic obstruction are uncommon, although edema and granulation tissue may develop in the post‐operative period and necessitate close post‐operative monitoring. Laryngoscope, 133:6–14, 2023